Politik Identitas Dalam Pemilihan Gubernur Maluku Utara Tahun 2019 - Fakhrunnisa, Fakhrunnisa; Yusuf, Alma Nabila (Journal of Citizenship, 2022)
Abstract :This study discusses the existence of identity politics in the 2019 North Maluku gubernatorial election. In the 2019 North Maluku gubernatorial election, the couple successfully won with the help of identity politics so that they won the trust of the citizens. In this study, the research method used by the researcher is a qualitative research method. The data used in this study is in the form of secondary data, namely from books, journals, articles, social media and so on. The results of this study are that it can be seen that ethnic identity politics in the 2019 North Maluku gubernatorial election is a political reality that is consciously built by informal organizations and the main party structure, government, and government bureaucratic structures to strengthen nationalist groups in winning political support from the community. or ethnicity. The reconstruction of the national identity politics that prevailed in the PILKADA of North Maluku has also become a dominant political force in. Likewise, the role of informal actors outside the structure of political parties and the bureaucracy has also developed into a political machine that replaces it by supporting its existence and boldly appearing as supporters of candidates who are fighting for the life of the PILKADA.Keywords: identity politics, ethnic groups, multiculturalism.Â AbstrakPenelitian ini membahas tentang adanya politik identitas dalam pemilihan Gubernur Maluku Utara tahun 2019. Pada pilgub Maluku Utara tahun 2019, berhasil dimennagkan oleh pasangan dengan bantuan politik identitas sehingga mendapat kepercayaan dari warga. Pada penelitian ini, metode penelitian yang digunakan oleh peneliti yaitu metode penelitian kualitatif. Datayang digunakan pada penelitian ini yaitu berupa data sekunder yaitu dari buku, jurnal, artikel, media sosial dan lain sebagainya. Hasil dari penelitian ini yaitu dapat diketahui bahwa Politik identitas pada etnik dalam pemilihan gubernur Maluku Utara tahun 2019 merupakan realitas politik yang secara sadar dibangun oleh organisasi informal dan struktur partai utama, pemerintahan, serta struktur birokrasi pemerintah untuk memperkuat kelompok nasionalis pada memenangkan dukungan politik dari masyarakat atau suku bangsa. Rekonstruksi politik identitas nasional yang berlaku dalam PILKADA Maluku Utara juga menjadi kekuatan politik yang dominan pada. Demikian pula peran actor informal di luar struktur partai politik dan birokrasi juga berkembang menjadi mesin politik yang menggantikan dengan mendukung keberadaan dan dengan berani muncul sebagai pendukung calon yang berjuang hidup PILKADA.Kata kunci:Â  politik identitas, kelompok etnis, multikulturalisme.